COVID-19 and the need for stringent rules on data sharing - Krishan, Kewal; Kanchan, Tanuj (Acta Biomedica Atenei Parmensis, 2020)
This communication refers to the retractions of the two high profile COVID-19 papers of the top medical journals when the data analytics company declined to share the raw data of the papers. In this commentary, we emphasize that it is very pertinent for the journals to mandatorily ask the authors for sharing of the primary data. This will ensure data integrity and transparency of the research findings, and help in negating the publication frauds.